Peningkatan Kompetensi Guru SMKN 1 Malingping melalui Pelatihan Penggunaan Quizizz dan Wordwall untuk Optimalisasi Asesmen Formatif Berbasis Digital - Yayan Sudrajat; R.A. Annita Meilina Ahmadi; Ikeu Liana Dewi; Ina Herlina; Rifka Kamalia Wardani; Yadi Supriyadi (Pusat Riset dan Inovasi Nasional, 2025)
This community service program focuses on training teachers at SMKN 1 Malingping in developing formative assessment instruments using the Quizizz and Wordwall platforms. The main objective is to enhance teachers’ competencies in integrating technology into classroom assessment practices, thereby improving the quality of teaching and learning. Formative assessment plays a crucial role in the learning process as it allows teachers to continuously monitor student progress, identify learning gaps, and provide timely feedback that supports both remediation and enrichment. By mastering digital tools such as Quizizz and Wordwall, teachers can design engaging, interactive, and effective assessment activities that align with curriculum objectives while also increasing student motivation and participation. The training was conducted through a workshop model, combining theoretical sessions on formative assessment principles with hands-on practice in creating and implementing online quizzes, interactive games, and customized learning activities. Teachers were guided step-by-step in account creation, content development, and analyzing assessment results for instructional decision-making. Feedback sessions were also integrated to address challenges and share best practices. The results of the training indicated a significant improvement in teachers’ skills and confidence in utilizing Quizizz and Wordwall for formative assessment. Participants demonstrated the ability to design varied assessment formats, adapt content to students’ needs, and effectively interpret assessment data to inform teaching strategies. Moreover, teachers reported increased student engagement when these platforms were implemented in classroom settings. This program highlights the importance of equipping educators with digital literacy skills that are relevant to 21st-century learning demands. The integration of Quizizz and Wordwall not only streamlines the assessment process but also fosters a more dynamic and student-centered learning environment. The experience from SMKN 1 Malingping suggests that similar training initiatives can be replicated in other schools to promote effective, technology-based formative assessment practices.